Análise das despesas de pessoal à luz da Lei de Responsabilidade Fiscal nos estados brasileiros no período 2013 a 2022 - Foltz, Roberto Daniel (2024)
The Fiscal Responsibility Law (FRL) was established in 2000 as a fundamental regulatory framework for fiscal management in Brazil. Its purpose is to ensure the balance of public accounts and promote transparency in resource administration. A crucial aspect of the FRL is the definition of limits for personnel expenses, aiming to prevent an excessive commitment of revenues. In this context, this research aims to analyze the relationship between personnel expenses of the Executive Powers of Brazilian States from 2013 to 2022, considering various socio-economic variables. It intends to investigate how this relationship is influenced by factors such as economic wealth, unemployment, education, tax burden, population density, inflation, political cycles, and economic shocks, including the COVID-19 pandemic. The study uses an empirical approach, analyzing annual personnel expenditures of the 26 Brazilian states over a decade, through a panel data linear regression model. The results indicate a significant and negative impact of the tax burden on the relationship between personnel expenses and net current revenue. Additionally, the presence of the pandemic demonstrated a statistically significant negative effect on this relationship. These findings contribute to the understanding of fiscal management and public policy, suggesting the need for future research to further explore the interaction between tax burden and public spending, considering its implications in other areas of state budgets.